Fall related self efficacy: A significant barrier for physical activity in ambulatory multiple sclerosis patients (Annals of Medical Research, 2021)
Aim: Increasing the level of physical activity in multiple sclerosis (MS) patients is very important to cope with the symptoms associated with disease. The aim of this study was to analyze the psychosocial and physical barriers related to physical activities in MS patients.Material and Methods: Fifty four MS patients who were able to walk at least 100 meters without walking aids were enrolled in this study. The patients were evaluated for their level of physical activity, walking distance, severity of pain and fatigue, fall related self-efficacy and their level of social support.Results: There were no correlation was found between the level of physical activity and the negative symptoms of pain and fatigue (rho: 0.-256 p: 0.06- rho: -0.218 p: 0.112 respectively). While the correlation of the level of physical activity with the level of ambulation was low, that of the fall related self-efficacy was found to be moderate (rho: -0.590, p=0.000). Additionally, no correlation was found with the level of social support (rho: -0.185, p=0.181). Conclusion: Pain and fatigue alone do not effect physical activity level in MS patients. However, fall related self-efficacy is a significant predictor of physical activity. It should not be ignored in programs aimed towards increasing physical activity.
Keywords: Multiple sclerosis; physical activity; fall related self-efficacy; fear of falling